2010
DOI: 10.1152/jn.00483.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Central Nervous System Does Not Minimize Energy Cost in Arm Movements

Abstract: . It has been widely suggested that the many degrees of freedom of the musculoskeletal system may be exploited by the CNS to minimize energy cost. We tested this idea by having subjects making point-to-point movements while grasping a robotic manipulandum. The robot created a force field chosen such that the minimal energy hand path for reaching movements differed substantially from those observed in a null field. The results show that after extended exposure to the force field, subjects continued to move exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 38 publications
(52 reference statements)
3
81
1
Order By: Relevance
“…Training subjects to use nonpreferred trajectories is difficult and hinders the ability to experimentally test whether movement trajectories are chosen to minimize metabolic cost (Alexander, 1997). In a recent study, subjects continued to move in a relatively straight line path to the target, even though it required greater end-point work than a curved movement path that was designed to be the minimum end-point work path (Kistemaker et al, 2010). They concluded that the CNS does not minimize metabolic cost.…”
Section: Discussionmentioning
confidence: 99%
“…Training subjects to use nonpreferred trajectories is difficult and hinders the ability to experimentally test whether movement trajectories are chosen to minimize metabolic cost (Alexander, 1997). In a recent study, subjects continued to move in a relatively straight line path to the target, even though it required greater end-point work than a curved movement path that was designed to be the minimum end-point work path (Kistemaker et al, 2010). They concluded that the CNS does not minimize metabolic cost.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental setup was similar to that used in a previous study (Kistemaker et al 2010; see Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The 1-DOF and 2-DOF musculoskeletal models of the arm used in this study (Fig. 2) have been described in full detail elsewhere (Kistemaker et al 2006(Kistemaker et al , 2007b(Kistemaker et al , 2010see also van Soest and Bobbert 1993). In short, the 1-DOF model consisted of two rigid segments (representing forearm and upper arm) interconnected by two hinge joints (representing glenohumeral joint and elbow joint) and driven by four lumped muscle models.…”
Section: Musculoskeletal Models Of the Armmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate these signals or motor commands, a frequently used method is perturbing goal-directed arm movements with a mechanical load. (Bhushan and Shadmehr 1999;Debicki and Gribble 2004;Gottlieb 2000;Gribble and Ostry 2000;Hinder and Milner 2003;Izawa et al 2008;Kistemaker et al 2010;Smeets et al 1990, etc.). These researchers used the changes in movement kinematics in response to a mechanical perturbation to conclude what aspects of the movement are controlled and what information is used to customize motor commands to the external conditions.…”
Section: Introductionmentioning
confidence: 99%